Kuwait : Staff Report for the 2003 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2004)
The staff report for the 2003 Article IV Consultation on Kuwait highlights the economic developments and policies. The macroeconomic position over the medium term under current oil price expectations and the maintenance of a cautious policy stance is projected to weaken, but is not expected to pose sustainability issues. The implementation of the official reform program should be accelerated to further strengthen the fiscal position and create the institutional and legal environment needed for promoting private investment.